Global and National Consumption of Animal Source Foods for Children and Adults in 2015: Systematic Analysis of Country-Specific Nutrition Surveys Worldwide (P10-077-19). (13th June 2019) - Miller, Victoria; Micha, Renata; Cudhea, Frederick; Onopa, Jennifer; Shi, Peilin; Zhang, Jianyi; Reedy, Julia; Singh, Gitanjali; Webb, Patrick; Mozaffarian, Dariush
Abstract: Objectives: Global intakes of animal source foods (ASFs) are important for several health outcomes─ broadly positive for maternal and child health outcomes (MCH) and broadly negative for some non-communicable diseases (NCDs). While ASFs represent an important source of key nutrients for many (particularly lower-income) consumers, the distributions of ASF intake is not well established. Our objective was to generate comprehensive estimates of daily intakes of milk, eggs, unprocessed red meat, and additional ASFs by country, age, sex, education and urban/rural location in 2015. Methods: National and subnational surveys on dietary intake were identified through systematic searches of multiple electronic databases, and through personal communication with experts worldwide. Presently, the Global Dietary Database (GDD) includes 1137 survey-years of global data representing participants from 185 countries (97.5% of the world's population). Bayesian hierarchical modeling methods were used to combine individual-level intake data with country-level availability data and estimate mean intake and its statistical uncertainty for each country-, age-, sex-, education-, urban/rural- and year-specific stratum. Results: In 2015, global milk intake was 95.0 g/day (95% uncertainty interval [UI] 70.1–134.7 g/day) with region-specific intakes ranging from 49.2 g/day in Asia to 155.9 g/day in high-income countries (Figure 1). Mean national milk intake was highest in Sweden (299.9 g/day) and lowest in China (23.4 g/day). Global egg intake was 25.0 g/day (13.5–54.1 g/day). Region-specific intake was highest in Latin American and the Caribbean (45.4 g/day) and lowest in Sub-Saharan Africa (13.9 g/day; Figure 2). Mean national egg intake was ≥1 serving per day (55 g) in 3 of the 185 countries. Global unprocessed red meat intake was 57.9 g/day (40.1–89.2 g/day) and intake was greatest in the Former Soviet Union (75.3 g) and Latin America and the Caribbean (69.4 g; Figure 3). National red meat intake was ≥1 serving per day (100 g) in 7 of the 185 countries. Additional findings for cheese, yogurt, reduced fat milk, whole milk, seafood and processed meat will be presented at the meeting. Conclusions: Our findings highlight the substantial range of ASF intake worldwide. These data are valuable for dietary monitoring and the development of policies to prevent MCH and NCDs associated with both ASF insufficiency and surplus. Funding Sources: Gates Foundation. Supporting Tables, Images and/or Graphs: